Structure of planktonic community in the southern part of the Chukchi Sea in summer period - Alexander M. Slabinsky; Alexander L. Figurkin (Известия ТИНРО, 2014)
Results of plankton and oceanographic surveys conducted by Pacific Fish. Res. Center (TINRO) in the southern Chukchi Sea in August-September of 2003, 2007, 2008, and 2010 are presented. Plankton samples were collected by Juday BSD net (mesh size 0.168 mm) from the layer 0-200 m or 0-bottom on the shelf with towing velocity 0.7-1.0 m/s. The samples are processed according to standard techniques accepted in TINRO (Volkov, 1996). The net phytoplankton biomass varied in the range 80-1683 mg/m3, with mean value 728.0 mg/m3 (the surveys were conducted mostly in the period of phytoplankton bloom, with exclusion the year 2008 when its biomass was insignificant). It was usually heightened in two areas: in the southeastern Chukchi Sea influenced by water advection from the Bering Sea and in the waters of the Siberian Coastal Current entered to the western Chukchi Sea. The zooplankton biomass had a tendency to increase year by year because of increasing of all species groups abundance, in particular Chaetognatha. Species structure of zooplankton was rather stable, with permanent 3-4 dominant species with summary portion > 50 % of total biomass, though some year-to-year changes of their percentage were observed. These changes, as well as spatial differences of the species structure, are linked with water exchange and depend on water transport through the Bering Strait and the western boundary of the Chukchi Sea and distribution of the entered waters, which improve productivity of the southern Chukchi Sea and enrich its fauna.